Location Optimization of Multidistribution Centers Based on Low-Carbon Constraints - Peixin Zhao; Bo Liu; Lulu Xu; Di Wan (Discrete Dynamics in Nature and Society)
Location optimization of distribution centers is a systematic and important task in logistics operations. Recently, reducing carbon footprint is becoming one of the decision-making factors in selecting the locations for distribution centers. This paper analyzes the necessity of industrial carbon dioxide emission cost internalization in four aspects and builds a model for multidistribution centers location in effort of reducing carbon footprint that can provide optimized strategy support for decision makers and logistic operators. Numerical examples are presented to illustrate the feasibility and effectiveness of the models.